2023
DOI: 10.1371/journal.pone.0281963
|View full text |Cite
|
Sign up to set email alerts
|

A moderated mediation model to predict the adoption intention of renewable wind energy in developing countries

Abstract: Developing countries are deprived of resources, and their economies are dwindling. Energy shortfall is one of the leading issues in developing countries that not only shatter economies but is the leading cause of depletion of natural resources and environmental pollution. There is an urgent need to shift to renewable energy sources to save economies and natural resources and to save our ecological system. Aiming for this, we have collected a cross-sectional data set to study the household intentions of shiftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…The study result indicates that important stakeholders and the business community play significant roles in driving the intention to use solar technology. The research finding is consistent with studies on the acceptance of renewable energy technology proposed by Kardooni et al (2016), Adepoju & Akinwale (2019), Aggarwal et al (2019), Khazaei (2019), Masrahi et al (2021), Mustafa et al (2023).…”
Section: Test the Research Hypothesessupporting
confidence: 90%
See 1 more Smart Citation
“…The study result indicates that important stakeholders and the business community play significant roles in driving the intention to use solar technology. The research finding is consistent with studies on the acceptance of renewable energy technology proposed by Kardooni et al (2016), Adepoju & Akinwale (2019), Aggarwal et al (2019), Khazaei (2019), Masrahi et al (2021), Mustafa et al (2023).…”
Section: Test the Research Hypothesessupporting
confidence: 90%
“…The intention to invest in renewable energy technology is influenced by family members (Poier, 2021), friends (Rai & Robinson, 2015), and significant others (Havas et al, 2015). In the field of renewable energy, several studies have shown the positive impact of social influence on the intention to use renewable energy technology (Kardooni et al, 2016, Adepoju & Akinwale, 2019Aggarwal et al, 2019;Khazaei, 2019;Masrahi et al, 2021;Mustafa et al, 2023). Therefore, the study suggests research hypothesis H3: Social influence positively affects the intention to use solar technology by enterprises.…”
Section: Research Hypothesesmentioning
confidence: 84%
“…For some entrepreneurs, the main objective may be to achieve maximum financial return in the short term, without necessarily focusing on sustainability or long-term social and environmental impact. On the other hand, Mustafa et al [1] stated that if entrepreneurs and others are aware of the benefits that their business can have on the environment, they would be much more determined to invest in biomass-based renewable energy. Yi [62] claims that a rather important role in environmental protection is green entrepreneurship, and an important factor for achieving this requirement is the implementation of ecological entrepreneurial education in school.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the demand and need for energy, special attention is paid to alternative sources of renewable energy, such as wind energy, solar energy or energy produced from biomass. Renewable energy, unlike thermal energy, also contributes to sustainable development, as it does not result in any direct emission of greenhouse gases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results suggest that the proposed system can work under variable weather and load conditions. Work has been on predictions models to predict the adoptions of renewable wind energy in developing countries [ 3 ]. The article by Barbosa et al describes a study that calculates the feasibility and cost of implementing a 100% renewable energy-based power system in South and Central America by 2030, using an hourly resolved energy model [ 4 ].…”
Section: Introductionmentioning
confidence: 99%